2022
DOI: 10.1007/s11606-021-07231-4
|View full text |Cite
|
Sign up to set email alerts
|

Sitting at the Bedside: Patient and Internal Medicine Trainee Perceptions

Abstract: Background Sitting at the bedside may strengthen physician–patient communication and improve patient experience. Yet despite the potential benefits of sitting, hospital physicians, including resident physicians, may not regularly sit down while speaking with patients. Objective To examine the frequency of sitting by internal medicine residents (including first post-graduate year [PGY-1] and supervising [PGY-2/3] residents) during inpatient encounters and to assess the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
(33 reference statements)
0
13
2
Order By: Relevance
“…Another proven strategy is sitting at the bedside. [15][16][17][18] A significant difference was found between patients' perception of time and actual time spent at the bedside. 15 In one study, the actual length of time the physician stood at the bedside was 1 minute 28 seconds; however, patients perceived them at the bedside an average of 3 minutes 44 seconds.…”
Section: Sit At the Bedsidementioning
confidence: 97%
See 1 more Smart Citation
“…Another proven strategy is sitting at the bedside. [15][16][17][18] A significant difference was found between patients' perception of time and actual time spent at the bedside. 15 In one study, the actual length of time the physician stood at the bedside was 1 minute 28 seconds; however, patients perceived them at the bedside an average of 3 minutes 44 seconds.…”
Section: Sit At the Bedsidementioning
confidence: 97%
“…Another proven strategy is sitting at the bedside 15–18 . A significant difference was found between patients’ perception of time and actual time spent at the bedside 15 .…”
Section: Strategies For Successmentioning
confidence: 99%
“…7 Simple, modifiable physician behaviors, such as sitting at the hospital bedside, may improve patient-clinician communication. [8][9][10][11][12][13] Sitting has been associated with improvements in patients' perceived understanding of their condition and with patients perceiving that clinicians spend more time at the bedside, without actually making clinical encounters take longer. 8,11 Despite these potential benefits, hospital clinicians do not regularly sit during patient interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Sitting has been associated with improvements in patients' perceived understanding of their condition and with patients perceiving that clinicians spend more time at the bedside, without actually making clinical encounters take longer. 8,11 Despite these potential benefits, hospital clinicians do not regularly sit during patient interactions. 8,9,14 In a recent study at our institution, the majority of hospitalized patients (56%) reported that internal medicine residents never sat at the bedside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation